2009
DOI: 10.19173/irrodl.v10i4.617
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Advanced Certificate in Education (ACE) Program on the Professional Practice of Graduates

Abstract: This paper examines the impact of a distance education program offered by the University of Pretoria, South Africa, on the professional practice of teachers. A pilot study was conducted using a combination of surveys and focus group interviews. Findings reveal that the program was beneficial to graduates’ personal development, professional practice, schools, learners, and colleagues. Further, principals who participated in the study attested to the differences they observed between the graduates and other tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Survey instruments have been identified as being the most popular data collection tools in outcomes measurements and evaluation (Aluko, 2009;Sampson, 2003). Two questionnaires were used to gather data about the student-lecturers' views of the VEOP at the UFS.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Survey instruments have been identified as being the most popular data collection tools in outcomes measurements and evaluation (Aluko, 2009;Sampson, 2003). Two questionnaires were used to gather data about the student-lecturers' views of the VEOP at the UFS.…”
Section: Methodsmentioning
confidence: 99%
“…The questions in the second survey were also based on the learning outcomes of the programme, as well as the principles that guide the programme (cf. Aluko, 2009). The researchers, furthermore, entered into lengthy discussions with the dean and the director of short courses at SOL to determine their perspectives on VEOP, their expectations of the evaluative study, and their views on the future of VEOP at SOL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, not much has been done to measure the impact of distance education training programmes on the professional practice of teachers (Fahy, Spencer and Halinski, 2007;Aluko, 2009). Research has shown that reports emanating from such evaluations can reveal the strengths and weaknesses of programmes, and can be used to improve them if necessary (Newcomer and Allen, 2008).…”
Section: Introductionmentioning
confidence: 99%